Inter radicular bone dimensions in primary stability of immediate molar implants - A cone beam computed tomography retrospective analysis - Arshad Jamal Sayed; Safia Shoeb Shaikh; Shoeb Yakub Shaikh; Mohammed Aabid Hussain (Elsevier, 2021)
Purpose: The purpose of the study was to analyze the dimensions of socket morphology, interradicular bone dimensions, root length and morphology, buccal cortical bone thickness and gap defect between the implant bone in mandibular molars with cone beam computed tomography (CBCT) for immediate molar implant (IMI) placement. Materials and methods: Sample sizes of 300 mandibular 1st and 2nd molars were each selected from the CBCT scans by inclusion and exclusion criteria. CBCT measurements were performed for socket size morphology, mesiodistal width, and buccolingual cancellous bone width at the crest at the apex. Width of the buccal cortical plate at the crest and interradicular bone (IRB) at the apex, 3 mm cervical to the apex and 6 mm cervical to the apex. Vertical parameters from the crest to furcation (L1), length from furcation to the apex (L2) and mesiodistal root morphology were measured to analyze the root configuration. Results: All the parameters were analyzed for descriptive statistics for the mean and standard deviation. The majority were of Type B and C socket morphology with peri-implant bone defects of 2-2.5 mm, and the interradicular bone septum (IRB) was moderate for both first molar (1 M) and second molar (2 M) sites, but 2 M was shown to have less IRB than 1 M. Adequate buccal cortical bone thickness of 1.1 mm to 1.4 mm and buccolingual cancellous bone width were measured for both the 1 M and 2 M sites. Conclusion: The morphology of the molar extraction socket determines the adequate stability for IMI. In mandibular molar teeth, where interradicular bone is incompetent in providing good primary stability, in addition to interradicular bone, clinicians should look for support from the apical bone and interdental septal bone for attaining primary stability of IMI.